2011
DOI: 10.1097/ico.0b013e31820009bc
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Effects of Overnight Orthokeratology on Corneal Cell Morphology and Corneal Thickness

Abstract: OK lenses for myopia induce significant structural and optical changes particularly in the central epithelium after 15 days or 1 month of wear. The central corneal epithelium responds to OK wear by undergoing significant epithelial cell shape and size alterations with no effects, however, on the cells of the corneal endothelium or the corneal stroma. Peripheral corneal thickness increased with respect to baseline values. These findings suggest that the corneal epithelium is the principal structure affected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
47
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 49 publications
4
47
0
4
Order By: Relevance
“…Nieto-Bona et al 11,13 also noted Positive values shown in the Δ column correspond to a rise in the parameter value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nieto-Bona et al 11,13 also noted Positive values shown in the Δ column correspond to a rise in the parameter value.…”
Section: Discussionmentioning
confidence: 99%
“…However, although its effects on corneal topography, visual acuity, contrast sensitivity, optical quality of the eye, and biomechanical properties have been widely investigated, [5][6][7][8][9][10] only a few studies have examined the histological effects of this technique on the morphology of the human cornea. [11][12][13] In 2011, Nieto-Bona et al 13 published the results of a year-long clinical study including individuals who wore OK lenses daily. This study reported corneal structural and optical changes.…”
mentioning
confidence: 99%
“…[13][14][15] Some studies have also determined OK effects on tear film components, 16 such as inflammatory mediators. 17 These studies conducted both in animals [18][19][20] and humans 6,7,12 have identified corneal changes produced in stromal and epithelial cell density, SBNP thickness and distribution, 7,12 and epithelial layer thickness ans also changes in the levels and distribution of proinflammatory mediators in the tear film samples of OK wearers. 17,21 To date, however, the effects of OK treatment on tear film osmolarity (TFO ) have not yet been examined.…”
mentioning
confidence: 99%
“…5 The success of OK has been accompanied by a need to address the corneal response to treatment. Recent research efforts have examined changes in corneal morphology and physiology by assessing the effects of treatment on cell density, [6][7][8] thicknesses of the corneal layers, [9][10][11] subbasal nerve plexus (SBNP) distribution, 7,12 and corneal biomechanics. [13][14][15] Some studies have also determined OK effects on tear film components, 16 such as inflammatory mediators.…”
mentioning
confidence: 99%
“…Lenses are worn during sleep and removed on waking to temporarily correct refractive error, thereby providing clear, unassisted vision throughout the day. 23 Many studies have shown that OK-induced changes to the corneal contour are the result of changes in the epithelial layer [24][25][26][27] ; however, no studies have investigated the effects of OK treatment on the SBNP. Furthermore, several researchers have suggested that sub-basal nerves and epithelial cells migrate in tandem, 21,[28][29] so an investigation of SBNP changes during OK treatment may increase our understanding of epithelial layer changes during this modality of contact lens wear.…”
mentioning
confidence: 99%